INDONESIAN PERSPECTIVE ON THE INVESTOR–STATE DISPUTE SETTLEMENT MECHANISM FOR FOREIGN INVESTMENT DISPUTE SETTLEMENT IN THE FIELD OF INTELLECTUAL PROPERTY RIGHTS - Leonard, Jessica; Amalia, Prita; Chandrawulan, An An (UI Scholars Hub, 2020)
Investment includes tangible and intangible assets. Intangible assets are often connected with intellectual property which leads to intangible results. The lack of “visibility” in intangible assets makes them difficult to measure. Current international regulations have not also explicitly provided room for enforcement regarding intellectual property rights in terms of foreign investment. Therefore, an emergence of cases is observed in investment disputes within the field of intellectual property rights through the Investor–State Dispute Settlement (ISDS) mechanism. In this research, we discuss cases of foreign investment disputes in such a field. From these cases, we find the factors that determine the occurrence of foreign investment disputes in the field of intellectual property rights. The ISDS mechanism can be used to resolve foreign investment disputes in the field of intellectual property. Furthermore, this research discusses the perspective of Indonesian law regarding foreign investment disputes in the mentioned field by using the ISDS mechanism. Qualitative methods and secondary data analysis are also used. The research aims to discover and identify foreign investment disputes in the field of intellectual property rights.